(untitled) (Journal of the Management Sciences, 2024)
The study investigated the extent to which colour of goods stimulate impulse buying among lecturers. The study was a descriptive survey design and involved a population of 317 female lecturers drawn from six Universities in the North East Nigeria. No sample was drawn for the study as the entire population of 317 was surveyed. The instrument for data collection was a structured questionnaire which was also face validated by three experts from the University of Nigeria Nsukka while one came from Abubakar Tafawa Balewa University Bauchi. The instrument was tested for reliability using the Cronbach Alpha formula and obtained a coefficient of 0.80. The research questions were answered using Mean while the Null hypotheses were tested using ANOVA at 0.05 level of significance. The major findings were that colour of goods, constitute to a high extent, determinants of female lecturers’ impulse buying. It was therefore recommended, among others, that retailers should utilize the findings of the study to develop better strategies to attract significant share of consumers’ impulse purchases. It was also recommended that, while impulse buying should be accorded the status or recognized marketing concepts, consumers should be cautious in engaging in impulse buying to avoid unnecessary disorganization of family and individual planning and budgeting as well as business collapses.